Iron Shadows Behind the Smile of Power: Torture Under the New Order Indonesia - Amrullah, Said; Ezzerouali, Souad; Ahmad, Miftahuddin (Indonesia Discourse, 2024)
This study critically examines the pervasive and systematic use of torture during Indonesia's New Order regime (1966-1998). This research underscores the urgent need to address the historical and ongoing implications of state-sponsored violence in Indonesia. Despite Indonesia’s transition to a democratic system, the legacies of repression and torture continue to shape the country’s political and social landscape. The study analyzes the mechanisms of torture under the New Order, focusing on the state's efforts to silence dissent, control political opposition, and maintain power through fear. Through an examination of archival materials, testimonies from victims, and interviews with human rights activists, this research illuminates the institutionalized practices of torture employed by the Indonesian military and police, often justified under the guise of national security and anti-communism. The work also highlights the impact of these practices on both individual lives and the broader society, contributing to a climate of fear that has persisted even after the regime’s downfall. This research makes a significant contribution by offering a comprehensive analysis of torture's role in reinforcing the power structures of the New Order, revealing the psychological and social costs of authoritarian rule. Furthermore, it emphasizes the urgent need for transitional justice and accountability mechanisms to address the crimes of the past. By providing a historical framework, the study advocates for a broader understanding of Indonesia’s political transformation, shedding light on the continuing struggle for justice and human rights in the post-New Order era.